Augmented reality in languages studying - Lunina, K. O.; Kulishova, N. E. (ХНУРЕ, 2020)
Nowadays Augmented Reality has rooted in our society, but this technology is still new and it develops from year to year. Some thirty years ago we could not imagine that this technology would be very useful and could change our lives.
Keywords: augmented reality; language learning